Image of a horseman on a bronze pin from the natural history museum Vienna - Makhortykh, S.; Grömer, K.; Tiefengraber, G. (Издательство Карагандинского университета имени академика Е.А. Букетова, 2024)
The article is devoted to the consideration of a bronze pin decorated with the cast figure of a horseman. It comes from burial № 1 (1884) of the famous Koban cemetery and is kept in the Natural History Museum in Vienna.
Венадағы табиғи тарих мұражайының қола түйреуішіндегі шабандоздың бейнесі
Изображение всадника на бронзовой булавке из музея естественной истории в Вене
Keywords: Koban culture; Natural History Museum Vienna; bronze pin; horseman; bow